Teacher’s Strategy in Growing Student Creativity through the Pancasila Student Profile Strengthening Project - Doni Ferdiansyah; Honest Ummi Kaltsum (Jurnal Ilmiah Sekolah Dasar, 2023)
The low character of students, one of which is the level of creativity possessed by students, has decreased after experiencing online learning due to Covid-19. The purpose of this study was to analyse the teacher's strategy in fostering student creativity through project learning to strengthen Pancasila students and to describe the constraints experienced by the teacher and the solutions made by the teacher in carrying out project learning. This study uses a descriptive qualitative approach with a phenomenological model. The subjects in this study were teachers and 4th-grade elementary school students. Researchers collect data through observation, interviews, and documentation. The data analysis technique used is an interactive model from Miles and Haberman. The results showed that teachers used two strategies in cultivating students' character and creativity: differentiation learning and project learning to strengthen the Pancasila student profile. Constraints found in addition to the low creativity of students are the limited references to the independent curriculum books for grades 1 and 4, the low availability of facilities, and project learning support tools. Another obstacle is time management because project-based learning usually takes a long time. For this reason, the teacher needs the right strategy to foster student creativity. It is hoped that the implications of this research can be studied in more depth to complement and be used as a basis for other research.